A indústria do brincar - Ferreira, Sueli Camargo (1992)
Playing is a constructive activity through which the child elaborates his/her perception of the world, and so, his/her personality. Toys can be used as instruments of creation when they allow the child to release his/her fantasies, or of domination when they reinforce the reproduction of ideas, values and social roles. It is necessary to know the universe around the child: the family, the society In which they live, so that we can evaluate the toys which are displayed at the market, the behaviors of parents in relation to the entertainment of the child and the parents's choice when they give toys to the child. Nowadays the society puts toys at the child's disposal that bring messages that reinforce social conducts by acting, from the beggining, in the creation of a way of thinking that is typically capitalist. The aim is to develop with the children's plays a kind of 'modelling of the behavior', which is playfull and semiotics at the same time. For a better understanding of 'the game rules', the characteristics of the society were examined with the support of three Marxist categories: work, alienation and merchandise. AIso, by trying to understand this new version of 'the child 's play', the following references were used: time, simulacrum, advertisement and consumption. This last one is detached from the others, because it is the base of the capitalist society. Nowadays, to consume becomes an imperative. Everybody is involved in it: men, women and children. Desire is the raw material, the creator of consumption. It leads the man to chase the ideal object incessantly. Desire can be seen as a formation of lack, constituted in the early days af the child' s life which, in a psychoanalytic view, invalves the person with an endless search. It alsa can be seen as a callecti ve praduction af the man, a pracess of breaking with the system that apresses him, accarding to Deleuze and Guattari. The 'appropriatian' of the child's wish by the toy is, surely, a powerful instrument that leads not anly to the exploratian af cansumption, but also to a subjectivity canstructed upon values that refer only to market's economy.